2010
DOI: 10.1590/s1677-55382010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of renal cell carcinoma clear cell type

Abstract: Purpose: The determination of prognosis in patients with renal cell carcinoma (RCC) is based, classically, on stage and histopathological aspects. The metastatic disease develops in one third of patients after surgery, even in localized tumors. There are few options for treating those patients, and even the new target designed drugs have shown low rates of success in controlling disease progression. Few studies used high throughput genomic analysis in renal cell carcinoma for determination of prognosis. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Freund and colleagues have also reported that CXCL8/IL-8 mRNA expression is 80-fold higher in MDA-MB-231 than in MCF7 cells (39). Furthermore, our data are in agreement with studies reporting CXCL8/IL-8 expression in a variety of human cancer cell lines, including renal carcinoma cells (40), melanoma cells (26,41,42), breast cancer cells (43), prostate cancer cells (44), colon carcinoma cells (45), and bladder cancer cells (46). Also, these studies associated CXCL8/IL-8 expression and the metastatic potential of the cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Freund and colleagues have also reported that CXCL8/IL-8 mRNA expression is 80-fold higher in MDA-MB-231 than in MCF7 cells (39). Furthermore, our data are in agreement with studies reporting CXCL8/IL-8 expression in a variety of human cancer cell lines, including renal carcinoma cells (40), melanoma cells (26,41,42), breast cancer cells (43), prostate cancer cells (44), colon carcinoma cells (45), and bladder cancer cells (46). Also, these studies associated CXCL8/IL-8 expression and the metastatic potential of the cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…RCCC is a genetic disease like other cancers which are caused by a series of genetic alterations [5] . Description of thousands of genomic sequences along with the technological development to identify the gene expression profiles on a large scale has provided a remarkable improvement in the analysis of carcinogenesis [25] . The improved technology may help us finding of possible therapeutic targets and identification of new diagnostic and prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…CTEPH is a polygenic disorder, resulting from genetic alterations. The description of thousands of genomic sequences, along with technological developments enabling the identification of gene expression profiles on a large scale, have improved the understanding of the pathogenesis of a number of diseases, including cancer ( 34 ). These advances may also facilitate the development of novel therapeutic targets, as well as diagnostic and prognostic markers.…”
Section: Discussionmentioning
confidence: 99%